Cryptic exon splicing function of TARDBP interacts with autophagy in nervous tissue. Issue 8 (3rd August 2018) - Torres, Pascual; Ramírez-Núñez, Omar; Romero-Guevara, Ricardo; Barés, Gisel; Granado-Serrano, Ana B.; Ayala, Victòria; Boada, Jordi; Fontdevila, Laia; Povedano, Monica; Sanchís, Daniel; Pamplona, Reinald; Ferrer, Isidro; et al.
ABSTRACT: TARDBP (TAR DNA binding protein) is one of the components of neuronal aggregates in sporadic amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration. We have developed a simple quantitative method to evaluate TARDBP splicing function that was applied to spinal cord, brainstem, motor cortex, and occipital cortex in ALS (n = 8) cases compared to age- and gender-matched control (n = 17). Then, we quantified the abundance of a TARDBP-spliced cryptic exon present in ATG4B (autophagy related 4B cysteine peptidase) mRNA. Results of these analyses demonstrated that the loss of this TARDBP function in spinal cord, brainstem, motor cortex, and occipital cortex differentiated ALS from controls (area under the curve of receiver operating characteristic: 0.85). Significant correlations were also observed between cryptic exon levels, age, disease duration, and aberrant mRNA levels. To test if TARDBP function in splicing is relevant in ATG4B major function (autophagy) we downregulated TARDBP expression in human neural tissue and in HeLa cells, demonstrating that TARDBP is required for maintaining the expression of ATG4B . Further, ATG4B overexpression alone is sufficient to completely prevent the increase of SQSTM1 induced by TARDBP downregulation in human neural tissue cells and in cell lines. In conclusion, the present findings demonstrate abnormal alternative splicing of ATG4B transcripts in ALS neural tissue in agreement with TARDBP loss of function, leading to impaired autophagy. Abbreviations : ALS: amyotrophic lateral sclerosis; ATG4B : autophagy related 4B cysteine peptidase; AUC: area under the curve; FTLD: frontotemporal lobar degeneration; iPSC: induced pluripotent stem cells; ROC: receiver operating characteristic; TARDBP : TAR DNA binding protein; RT-qPCR: quantitative RT-PCR